2017
DOI: 10.1039/c6mb00387g
|View full text |Cite
|
Sign up to set email alerts
|

The emerging picture of CDK9/P-TEFb: more than 20 years of advances since PITALRE

Abstract: CDK9 is a prominent member of the transcriptional CDKs subfamily, a group of kinases whose function is to control the primary steps of mRNA synthesis and processing by eukaryotic RNA polymerase II. As a cyclin-dependent kinase, CDK9 activation in vivo depends upon its association with T-type cyclins to assemble the positive transcription elongation factor (P-TEFb). Although CDK9/P-TEFb phosphorylates the C-terminal domain of RNAP II in the same positions targeted by CDK7 (TFIIH) and CDK8 (Mediator), the former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 164 publications
2
62
0
Order By: Relevance
“…Accumulating evidences indicate that CDK9 has an important role in cell growth, antiapoptosis, inflammatory responses, and resistance to therapies (29)(30)(31). In accordance with previous studies, we find that CDK9 acts as a functional protein that affects tumor cell proliferation, and knockdown of CDK9 significantly inhibited cervical tumor growth in both cervical cancer SiHa and CaSki cells.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidences indicate that CDK9 has an important role in cell growth, antiapoptosis, inflammatory responses, and resistance to therapies (29)(30)(31). In accordance with previous studies, we find that CDK9 acts as a functional protein that affects tumor cell proliferation, and knockdown of CDK9 significantly inhibited cervical tumor growth in both cervical cancer SiHa and CaSki cells.…”
Section: Discussionsupporting
confidence: 91%
“…It was shown that CycT1b could interact with CDK9, which is the only known kinase for RNAPII hyperphosphorylation [Dos Santos Paparidis et al, 2016;Gao et al, 2013]. The central question will be whether the binding of CycT1b to CDK9 is sufficient to activate its kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…8), indicating that CycT1b may negatively control the transcription of a broad range of host genes. It was shown that CycT1b could interact with CDK9, which is the only known kinase for RNAPII hyperphosphorylation [Gao et al, 2013;Dos Santos Paparidis et al, 2017]. The central question will be whether the binding of CycT1b to CDK9 is sufficient to activate its kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…CDKs have other functions beyond direct cell-cycle regulation ( Table 1) (66,76,114,(124)(125)(126)(127)(128)(129)(130). Additionally, CDKs that regulate gene transcription are of increasing interest as potential therapeutic targets in cancer (130)(131)(132).…”
Section: Cdk Inhibitors As Cancer Therapeuticsmentioning
confidence: 99%